Impact of home confinement during COVID-19 pandemic on Parkinson's disease. (November 2020) - Kumar, Niraj; Gupta, Ravi; Kumar, Hrishikesh; Mehta, Sahil; Rajan, Roopa; Kumar, Deva; Kandadai, Rukmini Mridula; Desai, Soaham; Wadia, Pettarusp; Basu, Purba; Mondal, Banashree; Sanchita,; et al.
Highlights: Parkinson's disease symptoms worsened during home confinement. Difficulty in availing formal neurology consultations and/or medicines. Quality of life in Parkinson's disease patients declined during home confinement. Use of telemedicine may benefit patients.